IMPLEMENTASI WEB SERVICE PADA SISTEM LAPORAN ARUS KAS DENGAN METODE RESTFUL API STUDI KASUS YAYASAN RUMAH DERMAWAN INDONESIA - Lestari, Sri; Haidar, Dzaky (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Rumah Dermawan Indonesia Foundation is a foundation engaged in the humanitarian field in Tangerang. In its activities, the Foundation encounters a problem in recording cash flow, because incoming and outgoing cash flows are still recorded on only one platform, making it less effective. The problem of recording cash flows will be more effective if you use a web service system to facilitate recording of incoming and outgoing cash flows. The model method used to record cash flows on the right web service system for this problem is the REST-Ful API which can be applied to the foundation. Therefore, the researcher proposed an idea that would be applied to the Foundation with the theme of a cash system report using the REST-Ful API method. From the method that the author uses, namely the REST-Ful API method, it shows that it can be used on more than one platform. So that in the future if there is development on other platforms it can be reused. Because the output generated from the REST-Ful API is JSON (Javascript Object Notation). To create a REST-Ful API, researchers will use the Golang language program, this is because the language is light when compiling and processing data.